Assessing Land Use/Land Cover Dynamic and Its Impact in Benin Republic Using Land Change Model and CCI-LC Products - Guidigan M.L.G.; Sanou C.L.; Ragatoa D.S.; Fafa C.O.; Mishra V.N. (My University, 2025)
Accurate information on land use/land cover (LULC) dynamics is necessary for the selection and execution of land use schemes to meet the increasing demands of basic human needs and welfare. This study aims to assess the LULC dynamics and its impacts in Benin using the climate change initiative land cover (CCI-LC) product within a GIS environment. The CCI-LC maps were acquired from the European Space Agency (ESA) for the years 2001, 2008 and 2013. The maps of 2001 and 2008 were used to simulate the LULC scenario for 2013 using Modules for Land Use Change Evaluation (MOLUSCE) available in QGIS software. The predicted result was compared with the observed LULC map of 2013 to validate the model. Finally, based on this, the prediction of future LULC scenario for years 2025 and 2037 was performed. The outcomes of this study revealed the rapid increase of cropland, forest and a considerable reduction of the Savannah land. © 2018, King Abdulaziz University and Springer Nature Switzerland AG.